The service of the state : [the IAS reconsidered] - Ghose, Bhaskar (New Delhi : Penguin Books India : Viking, 2011)
Memoirs of the author, an Indian diplomat.
Subtitle from jacket.
Keywords: Ghose, Bhaskar; Diplomats -- India -- Biography; India -- Foreign relations -- 20th century